Dosage Form Modification, a Simulation Activity between Nursing and Pharmacy Students - Chiao Xin Lim; Karen Livesay; Julie Stevens; Vivek Nooney; Katherine Baverstock; Nichole Orwin; Ieva Stupans (Pharmacy, 2022)
Background: The aim of this exploratory pilot study was to evaluate student perceptions of a simulation activity involving undergraduate nursing and pharmacy students. The key question was “how do nursing and pharmacy students respond in an immersive collaborative simulation activity which involves medication dosage form modification?” Methods: One hundred nursing students participated in a simulated exercise where patients required medications for which there were barriers to administration. Fourteen pharmacy students were also present in the simulated health environment, observing the work of the nursing students and being available to provide advice regarding medication administration to the nursing students. A mixed methods approach was employed for this exploratory pilot study, where both nursing and pharmacy students were invited to complete a survey regarding the experience at the end of the simulation exercise and pharmacy students completed a reflection. Both surveys and reflections were analyzed. Results: Survey results indicated very high satisfaction regarding the exercise for both pharmacy and nursing students. Analysis of pharmacy student reflections also indicated apprehension regarding their preparedness to contribute to the exercise, enjoyment in participation, their understanding of the value of collaboration between the two groups of students, and also recognition of their need to be more prepared for such situations. Conclusion: This study assessed student perceptions and did not formally evaluate learning outcomes. The interprofessional immersive simulated learning opportunity was viewed as valuable by both nursing and pharmacy students. The immersive simulation provided teaching staff with the opportunity to develop a new approach for the teaching of dosage form modification to both nursing and pharmacy students in an interprofessional setting.